Autosomal STR and SNP characterization of populations from the Northeastern Peruvian Andes with the ForenSeq™ DNA Signature Prep Kit. (May 2021) - Guevara, Evelyn K.; Palo, Jukka U.; King, Jonathan L.; Buś, Magdalena M.; Guillén, Sonia; Budowle, Bruce; Sajantila, Antti
Abstract: Autosomal DNA data from Peru for human identity testing purposes are scarce in the scientific literature, which hinders obtaining an appropriate portrait of the genetic variation of the resident populations. In this study we genetically characterize five populations from the Northeastern Peruvian Andes (Chachapoyas, Awajún, Wampís, Huancas and Cajamarca). Autosomal short tandem repeat (aSTR) and identity informative single nucleotide polymorphism (iiSNP) data from a total of 233 unrelated individuals are provided, and forensic genetic parameters are calculated for each population and for the combined set Northeastern Peruvian Andes. After correction for multiple testing in the whole dataset of the Northeastern Peruvian Andes, the only departure from Hardy-Weinberg equilibrium was observed in locus rs2111980. Twenty one out of 27 aSTR loci exhibited an increased number of alleles due to sequence variation in the repeat motif and flanking regions. For iiSNPs 33% of the loci displayed flanking region variation. The combined random match probability (RMP), assuming independence of all loci (aSTRs and iiSNPs), in the Chachapoyas, the population with the largest samples size ( N  = 172), was 8.14 × 10 -62 for length-based data while for sequence-based was 4.15 × 10 -67 . In the merged dataset (Northeastern Peruvian Andes; N  = 233), the combined RMP when including all markers were 2.96 × 10 -61 (length-based) and 3.21 × 10 -66 (sequence-based). These new data help to fill up some of the gaps in the genetic canvas of South America and provide essential length- and sequence-based background information for other forensic genetic studies in Peru. Highlights: A sample set from the Northeastern Peruvian Andes was studied. Length- and sequence-based data were obtained for 121 autosomal markers. Departure from Hardy-Weinberg equilibrium expectations was observed in rs2111980. For sequence variation, an increased number of alleles was observed in 21 aSTRs. The combined RMP were 2.96 × 10 -61 (length-based) and 3.21 × 10 -66 (sequence-based).